The Role of Strategic Agility in Achieving Competitive Advantage by Applying to Non-profit Organizations in Saudi Arabia - Hassan, Mahmoud (The Arab Journal of Administration, 2022)
This research entitled (The Role of Strategic Agility in Achieving Competitive Advantage by Applying to Non-Profit Organizations in Saudi Arabia) aimed to test the role of strategic agility in achieving the competitive advantage through applying it to non-profit organizations in Saudi Arabia. The research is aim to identify the role that strategic agility represents or plays in achieving competitive advantage by applying to non-profit organizations in KSA, through a set of sub-goals, which are to identify the concept and dimensions of strategic agility and to identify the concept and dimensions of competitive advantage, The problem of the study was an attempt to determine the role that strategic agility plays in achieving the competitive advantage of non-profit organizations in KSA. The sample comprised 100 participants from the employees in Saudi non-profit organizations. The strategic agility was measured through several dimensions: strategic sensitivity, selection of strategic objectives, clarity of vision, joint liability, core capabilities and collective commitment. The dimensions of the competitive advantage were represented in quality, efficiency, flexibility and creativity. The study concluded that the percentage of practicing strategic agility in Saudi non-profit organizations is high, the percentage of competitive advantage is high, and the dimensions of strategic agility have a positive and significant effect on quality, efficiency, flexibility and creativity. The study recommended the importance of adopting strategic agility in organizations due to its significant importance in achieving a competitive advantage, whether in for-profit or non-profit organizations, as is the case in the Saudi non-profit organizations under study.